2021
DOI: 10.1007/978-3-030-84570-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Pierre Teilhard de Chardin’s Phenomenology of the Noosphere

Abstract: Although Pierre Teilhard de Chardin (1881–1955) was thoroughly trained in philosophy and theology, he was first and foremost a paleoanthropologist, directly involved in the discovery of Homo erectus pekinensis (“Sinanthropus”) in China in the 1920s and 1930s. He came from a Catholic aristocratic background, was ordained a priest in 1911, survived World War I (as a stretcher-bearer, distinguished with the Legion of Honour), joined the Jesuit Order, conducted paleoanthropological field work during the interbellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…So, the concept of Omega point bears a profound teleological weight. Teilhard is credited of having anticipated the development of the internet, the network society, the Anthropocene and the Gaia theory (Brailas, 2019;Zwart, 2022). Teilhard's put an emphasis on the combination of the technological and biocultural evolution.…”
Section: Artificial Intelligence Singularity and A Meta-learning Ecol...mentioning
confidence: 99%
See 1 more Smart Citation
“…So, the concept of Omega point bears a profound teleological weight. Teilhard is credited of having anticipated the development of the internet, the network society, the Anthropocene and the Gaia theory (Brailas, 2019;Zwart, 2022). Teilhard's put an emphasis on the combination of the technological and biocultural evolution.…”
Section: Artificial Intelligence Singularity and A Meta-learning Ecol...mentioning
confidence: 99%
“…We observe that the use of the term rhizomatic develops in parallel with the use of the term Internet in the published corpus digitized by Google (Figure 3). Maybe Google itself can be understood as a developing learning rhizome trying to achieve an Omega point, the ultimate noosphere in the words of Teilhard de Chardin (Zwart, 2022). In a networking conception of learning, learners can be understood as autonomous, while interdependent, nomads creating and traversing their personal learning networks in their own ways in the context of a community of co-learners and in the context of a chaotic external environment of available learning resources and potential pathways.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to its originality, it has been suggested that thinkers, such as Antonio Stoppani, Vladimir Vernadsky, and Pierre Teilhard de Chardin, anticipated the concept (for Stoppani see Rull (2017); for Vernadsky see Guillaume (2014); for Teilhard de Chardin see Zwart (2022)). Teilhard de Chardin, for example, coined the term "noösphere" for a new world shaped by the advancement of humanity to a new stage of cognitive evolution, while Stoppani proposed the "Anthropozoic" as the name of a new Earth-historical period impacted by "human relicts", such as tools, weapons, buildings, and so on (Rull 2017, also see Trachtenberg 2015.…”
Section: How Original Is the Concept And Who Is Responsible For The A...mentioning
confidence: 99%